2009
DOI: 10.1080/00016340903002873
|View full text |Cite
|
Sign up to set email alerts
|

A novel antibiotic, linezolid, reduces intraperitoneal adhesion formation in the rat uterine horn model

Abstract: Linezolid was found to reduce intraperitoneal adhesion formation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 29 publications
0
6
0
2
Order By: Relevance
“…Nevertheless, current adhesion-prevention strategies are largely limited to mechanical barriers, such as oxidized regenerated cellulose (Gynecare Interceed, Ethicon, Inc., Somerville, NJ) or sodium hyaluronate with carboxymethylcellulose (Saprafilm, Genzyme, Inc., Cambridge, MA). While the effectiveness of these barrier agents in clinical practice remains inconsistent (7-9) other studies indicate that limiting inflammatory processes and/or angiogenesis may provide efficacy in reducing adhesion formation (10-12). …”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, current adhesion-prevention strategies are largely limited to mechanical barriers, such as oxidized regenerated cellulose (Gynecare Interceed, Ethicon, Inc., Somerville, NJ) or sodium hyaluronate with carboxymethylcellulose (Saprafilm, Genzyme, Inc., Cambridge, MA). While the effectiveness of these barrier agents in clinical practice remains inconsistent (7-9) other studies indicate that limiting inflammatory processes and/or angiogenesis may provide efficacy in reducing adhesion formation (10-12). …”
Section: Introductionmentioning
confidence: 99%
“…Multiple experimental studies using a variety of model systems have examined the efficacy of limiting inflammatory processes in an effort to reduce adhesion formation (12–15). For example, using a traditional animal model of adhesions, in which the peritoneal mesothelium is directly traumatized, investigators have demonstrated the effectiveness of sildenafil, resveratrol, and rosiglitazone in the inhibition of adhesion formation (1619).…”
mentioning
confidence: 99%
“…An array of antibiotics relevant to intra and post-operative care in sinus surgery were selected as treatments ( Table 1). Two oxazolidinone antibiotics were also selected due to emerging evidence that this class may facilitate a reduction in surgical adhesions (Aytan et al, 2009). Treatments were formulated using high concentration stock in cell media, at concentrations adapted from those reported in peer-reviewed literature when using common dosing regimens.…”
Section: Antibioticsmentioning
confidence: 99%